2008
DOI: 10.1073/pnas.0709320104
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional infrared spectra reveal relaxation of the nonnucleoside inhibitor TMC278 complexed with HIV-1 reverse transcriptase

Abstract: The two nitrile groups at the wings of the nonnucleoside HIV-1 reverse transcriptase (RT) inhibitor TMC278 are both identified in high-sensitivity 2D IR spectroscopy experiments of the HIV-1 RT/ TMC278 complex. The vibrational spectra indicate that the two arms of the inhibitor sense quite different environments within the hydrophobic pocket. The vibrational relaxation of the two arms are almost equal at 3 ps from model studies. The 2D IR spectra expose a significant distribution of nitrile frequencies that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
148
1
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(153 citation statements)
references
References 45 publications
3
148
1
1
Order By: Relevance
“…Crystal structures of the binding site between TMC278 and the HIV-1 RT complex, as well as freedom-of-motion analyses, revealed that TMC278 binds to the HIV-1 RT and adapts to changes in the NNRTI-binding pocket. TMC278 thereby compensates for the presence of drug resistance mutations, which further explains the mechanism of the increased genetic barrier to resistance to this compound (15,20 50 values ranging from 0.07 to 1.01 nM and 2.88 to 8.45 nM, respectively. TMC278 was on average approximately 10-to 15-fold less active against the HIV-1 group O isolates than against the HIV-1 group M primary isolates.…”
Section: Discussionmentioning
confidence: 97%
“…Crystal structures of the binding site between TMC278 and the HIV-1 RT complex, as well as freedom-of-motion analyses, revealed that TMC278 binds to the HIV-1 RT and adapts to changes in the NNRTI-binding pocket. TMC278 thereby compensates for the presence of drug resistance mutations, which further explains the mechanism of the increased genetic barrier to resistance to this compound (15,20 50 values ranging from 0.07 to 1.01 nM and 2.88 to 8.45 nM, respectively. TMC278 was on average approximately 10-to 15-fold less active against the HIV-1 group O isolates than against the HIV-1 group M primary isolates.…”
Section: Discussionmentioning
confidence: 97%
“…Two-dimensional IR spectroscopy probes the FFCF, and thereby the protein motions that are sensed by the transition-state analogue (the IR chromophore), only for a few tens of picoseconds at most. Although these experiments cannot identify the time scales for spectral diffusion for motions that occur beyond this time range, they do characterize the distribution of frequencies determined by the distribution of structures resulting from these slower motions (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)44). Motions at all time scales contribute to the initial value of the FFCF, but only those motions that occur on the femtosecond to picosecond time scale contribute to the FFCF decay probed in the 2D IR measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A close experimental approximation to this ideal is to study the dynamics of an enzyme in a complex with a transition-state-analog inhibitor. There have been several infrared spectroscopic studies of enzyme-ligand interaction dynamics with substrate-analog complexes that mimic the ground state (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). These studies use infrared echo and 2D IR spectroscopies to measure the frequencyfrequency time correlation function (FFCF) that reveals the time .…”
mentioning
confidence: 99%
“…Two 2D IR studies have been performed on biological systems using CN as the probe. One study involved HIV reverse transcriptase using a bound substrate containing a CN group (27). The other studied nitrile-labeled HP35 in its native state in water (28).…”
mentioning
confidence: 99%